Türkiye'de Elektronik İstihdam Platformlarında Yayınlanan Bilişim Sektörü İş İlanlarının Nitel Analizi (2017-2018) - Özkan, Yılmaz; Bingöl, Ufuk; Mete, Hakan (Muş Alparslan Üniversitesi, 2018)
In this study, It has been planned a qualitativedata analysis (QDA) of IT Sector’s job advertisements those were posted by themost popular Turkish Job Seeking Internet Portals. In this paper Inductiveanalysis is targeted and one of the sub-branch of QDA, “Content Analysis” isused. It is considered that the coding and analysis IT sector job advertisementthat contain data of labor requirement of IT Companies in one year, related toconstitute a source about possible arrangement for IT sector labor market inthe future.

Buçalışmada ülkemizde faaliyet gösteren önemli iş arama web sitelerinde 2017-2018döneminde yayınlanan bilişim sektörü iş ilanlarının niteliksel analizininyapılması hedeflenmiştir. Bu kapsamda NVivo programı ile nitel veri analizininbir alt unsuru olan içerik analizi çalışması yapılmıştır. Bir yıl içerisindebilişim sektöründe faaliyet gösteren firmaların ihtiyaç duyduğu işgücüne aitverilerin sergilendiği bilişim ilanları üzerinden gerçekleştirilen kodlama veanaliz çalışması ile sektörün istihdam yapısı incelenmiştir. Çalışmanın ileridegerçekleştirilecek bilişim sektörü işgücü piyasası düzenlemelerine kaynakoluşturacağı değerlendirilmektedir.
Qualitative Data Analysis of Information Technology Sector Job Advertisements Published on Electronic Employment Platforms in Turkey (2017-2018)
anemon
Keywords: Information Technology; Qualitative Data Analysis; Information Technology Job Advertisement; Bilişim; Bilişim İş İlanları; Nitel Veri Analizi